Red-Light-Driven Photocatalysis with NI-BODIPY-Fullerene Systems for Organic Transformations - Gunduz, Ezel Ozturk; Buyukpolat, Ummugulsum; Okutan, Elif (Springer/Plenum Publishers, 2025)
The direct use of low-energy red light for photochemical processes is attractive from a synthetic perspective but challenging to implement in practice. BODIPY-based photosensitizers (PSs) show considerable promise in this area due to their tunable photophysical properties. This study aims to explore the use of mono- and bis-adducts of heavy atom-free NI-BODIPY-fullerene triads, which strongly absorb red light in the 560 to 660 nm range, in red light-irradiated photocatalytic reactions. NI-BODIPY-fullerene photosensitizers possess the ability to generate singlet oxygen (O-1(2)), making them effective photosensitizers for the photocatalytic conversion of 1,5-dihydroxynaphtalene (DHN) to juglone and the photooxidation of thioanisole to methyl phenyl sulfoxide. Our photocatalysts are effective, with activities comparable to or even higher than those of readily available commercial systems, achieving 100% conversion of thioanisole to methyl phenyl sulfoxide within 2 h. This study highlights the potential of distyryl-NI-BODIPY-fullerene derivatives as promising photosensitizers/photocatalysts for applications in organic transformations.
Keywords: Borondipyrromethene; Fullerene; Napthalimide; Photocatalysis; Singlet oxygen